Competencia docente y la educación inclusiva en el nivel inicial - Ttito, Wendy (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the Universidad Nacional Micaela Bastidas de Apurímac, this study sought to determine the degree of relationship between teaching competence and inclusive education in public educational institutions at the initial level of the urban area of ​​the city of Abancay (Peru), 2020. The research was carried out at a basic level, of a relational type, with a non-experimental design and cross-section with a hypothetical-deductive method with a quantitative approach; The sampling was intentional non-probabilistic, obtaining a sample of 66 teachers. The research instruments used were the questionnaire for each of the study variables. Both instruments reached Cronbach's Alpha coefficients of .972 and .892, respectively, guaranteeing their reliability. The data obtained were statistically processed, obtaining descriptive and inferential results that allowed us to conclude that teaching competence has a positive, highly significant relationship. and high with inclusive education because the p value is equal to .000 and Kendall's Tau_ b is .556.